Metode RGEC untuk Menganalisis Kesehatan Bank di Bank BRI Syariah - Sari, Widya; Sadilah, Dea Nur (Universitas Ma'soem, 2021)
The background of this research is the fluctuation in financial ratios which is influenced by the amount of non-performing financing, the amount of third party funds released for financing, the ability of bank management to control the efficiency of the company, and the adequacy of capital owned by the bank. So that with the aim of knowing the level of bank soundness at BRI Syariah Bank for the period 2016 - 2020, an analysis is carried out according to the Financial Services Authority Regulation No. 8/POJK.03/2014 concerning the assessment of the soundness level of Islamic commercial banks and sharia business units, namely by using the RGEC method. In this study, the method used is a qualitative research with a descriptive approach. Secondary data is obtained from the BRI Syariah Bank Annual Report and the GCG Implementation Report published on the company's official website. Data collection was carried out by the author using documentation and literature studies. In this study, the steps taken in data analysis are data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the health level of BRI Syariah Bank according to the Risk Profile factor is Healthy and Very Healthy. The Good Corporate Governance factor received the title of Healthy. Earning factor obtained the predicate of Unhealthy and Unhealthy. And Capital Factor received the title Very Healthy.